The Igorot in the World Wide Web exploring the Igorot Ethnic Identity through the Communicative Act of Blogging - Rabia, Stephanie Luanne San Agustin (College of Arts and Letters, University of the Philippines Diliman, 2009)
The study entitled "The Igorot in the World Wide Web : exploring the Igorot Ethnic Identity through the Communicative Act of blogging" aimed toe determined how and why Igorot bloggers use their blogs as a means to actively represent themselves and assert their Igorot ethnic identities.